2023
DOI: 10.1680/jmuen.22.00023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of student pedestrian gap acceptance behaviour in suburban areas

Abstract: The safety of student pedestrians on suburban roads is an issue that is mainly overlooked. Numerous studies have been carried out on pedestrian crossing safety in developing countries. However, a study to identify factors that affect the gap acceptance behavior of student pedestrians on suburban roads is still lacking. Consequently, it is crucial to understand how factors influence pedestrians’ decisions. This motivated an investigation into student pedestrian crossing behavior at a crosswalk near a university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Kim ( 9 ) performed regression analysis and found that various facilities, such as raised medians, three-way intersections, street trees, parks, and recreational land use, increased the safety of aged pedestrians. Sheykhfard et al ( 10 ) identified factors affecting the safety of student pedestrians, focusing on crossing behavior at a crosswalk near a university campus. Lv et al ( 11 ) conducted Poisson regression and analyzed the relationship between aged pedestrians and built environments; roads’ green spaces, sidewalks, and intersections significantly affected the safety of these pedestrians, and green spaces only exerted their influence in an uncongested environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kim ( 9 ) performed regression analysis and found that various facilities, such as raised medians, three-way intersections, street trees, parks, and recreational land use, increased the safety of aged pedestrians. Sheykhfard et al ( 10 ) identified factors affecting the safety of student pedestrians, focusing on crossing behavior at a crosswalk near a university campus. Lv et al ( 11 ) conducted Poisson regression and analyzed the relationship between aged pedestrians and built environments; roads’ green spaces, sidewalks, and intersections significantly affected the safety of these pedestrians, and green spaces only exerted their influence in an uncongested environment.…”
Section: Literature Reviewmentioning
confidence: 99%